Australian dictionary of biography. 1991-1995, A-Z - Nolan, Melanie; Allbrook, Malcolm (Australian Dictionary of Biography Ser., 2021)
Volume 19 of the Australian Dictionary of Biography (ADB) contains concise biographies of individuals who died between 1991 and 1995. The first of two volumes for the 1990s, it presents a colourful montage of late twentieth-century Australian life, containing the biographies of significant and representative Australians. The volume is still in the shadow of World War II with servicemen and women who enlisted young appearing, but these influences are dimming and there are now increasing numbers of non-white, non-male, non-privileged and non-straight subjects. The 680 individuals recorded in volume 19 of the ADB include Wiradjuri midwife and Ngunnawal Elder Violet Bulger; Aboriginal rights activist, poet, playwright and artist Kevin Gilbert; and Torres Strait Islander community leader and land rights campaigner Eddie Mabo. HIV/AIDS child activists Tony Lovegrove and Eve Van Grafhorst have entries, as does conductor Stuart Challender, 'the first Australian celebrity to go public' about his HIV/AIDS condition in 1991. The arts are, as always, well-represented, including writers Frank Hardy, Mary Durack and Nene Gare, actors Frank Thring and Leonard Teale and arts patron Ian Potter. We are beginning to see the effects of the steep rise in postwar immigration flow through to the ADB. Artist Joseph Stanislaw Ostoja-Kotkowski was born in Poland. Pilar Moreno de Otaegui, co-founded the Spanish Club of Sydney. Chinese restaurateur and community leader Ming Poon (Dick) Low migrated to Victoria in 1953. Often we have a dearth of information about the domestic lives of our subjects; politician Olive Zakharov, however, bravely disclosed at the Victorian launch of the federal government's campaign to Stop Violence Against Women in 1993 that she was a survivor of domestic violence in her second marriage. Take a dip into the many fascinating lives of the Australian Dictionary of Biography.--Publisher's description.